Rebranding Kemasan Stik Ubi Ungu Desa Kroya guna Meningkatkan Nilai Jual Produk UKM - Indah Permatasari; Shinta Romadhona; Solichah Larasati (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Problems faced in selling purple sweet potato sticks include unattractive product packaging and very low selling prices, resulting in low profit margins. The purpose of this community service is to optimize the added value of the product by improving packaging quality. The methods applied include partner assistance, product development through rebranding the Purple Sweet Potato Stick Packaging, and training on Cost of Goods Sold (COGS). As a result of this community service activity, the purple sweet potato stick product now features packaging with nutritional adequacy information (AKG). The new, attractive packing not only enhances the perception of quality but also allows for more competitive pricing, thereby increasing the overall profit margin.